Integrating Computational Thinking and The Polya’s Model In Minecraft: The Effects on Learners’ Fractions Achievement - Tangkui, Rayner Bin (Indonesian Journal of Science and Mathematics Education, 2023)
There are few empirical research on the influence of incorporating computational thinking and Polya's Model in digital games on the academic achievement of students and the best ways for implementing this integration. Therefore, this quasi-experimental pretest and posttest non-equivalent group design research was aimed at determining the effect of integrating computational thinking and Polya’s model in Minecraft on students' fraction proficiency. Fifty-seven students from two intact classes were involved as the participants. The control group had 28 students, while the experimental group had 29 students. The findings revealed that the fraction achievement of the experimental group students increased as compared to students in the control group. It may be determined that studying fractions in Minecraft through the integration of computational thinking and Polya’s model had the best influence on student's academic progress. Thus, teachers should be able to incorporate it into other materials for learning mathematics.